Pemanfaatan Sosial Media Marketing Melalui Konten pada Instragram dalam Upaya Meningkatkan Brand Image Sebuah Produk - Puspasari, Dewi; Hadithya, Riyan (Jurnal Manajemen Bisnis dan Keuangan, 2023)
The rapid development of science and technology has led to changes in people's behavior towards fulfilling their daily needs. At this time promotional activities can be carried out through social media because it is felt to be the most effective in disseminating information quickly with a wide range. Promotion using social media is growing with the presence of various platforms used by companies or UMKM. Social media is a promotional tool that is very popular at this time. With social media, people can easily obtain various kinds of information about products or goods, the benefits of a product offered, product prices, and information on how to get these products or how to order them. The company's efforts to utilize social media as a digital promotional tool are expected to be able to provide many benefits for the business it runs, such as increased product sales and brand awareness of product brands that are increasingly recognized by the public. To make good product advertisements on social media, companies must pay attention to how good quality advertisements are presented and seen by internet users as potential customers. With good quality social media, it will increase product value in the eyes of consumers so that it will encourage increased brand loyalty.